AN UPDATED CHECKLIST AND A NEW SPECIES OF BEGONIA (B. RHEOPHYTICA) FROM MYANMAR. (1st April 2019) - Hughes, M.; Aung, M. M.; Armstrong, K.
Abstract : A new species, Begonia rheophytica (§ Platycentrum ), is described from northern Myanmar; it was initially confused with B. rhoephila, which is confined to Peninsular Malaysia. Comparison with other species with a rheophytic leaf shape is made. This new addition brings the number of currently recognised Begonia species in Myanmar to 73. An updated checklist of Myanmar Begonia species is also included.